2016
DOI: 10.1021/acs.jafc.6b03465
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and a Limonoid from the Fruits of Citrus unshiu and Their Biological Activity

Abstract: The fruits of Citrus unshiu are one of the most popular and most enjoyed fruits in Korea. As we continue to seek for bioactive metabolites from Korean natural resources, our study on the chemical constituents of the fruits of C. unshiu resulted in the isolation of a new flavonoid glycoside, limocitrunshin 1, along with seven other flavonoids 2-8 and a limonoid 9. All structures were identified by spectroscopic methods, namely 1D and 2D NMR, including HSQC, HMBC, and (1)H-(1)H COSY experiments, HRMS, and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…In our previous study, we found that methyl nomilinate showed an anti-inflammatory effect by inhibiting NO production by LPS-activated RAW 264.7 macrophages and significantly abrogated cisplatin-induced nephrotoxicity in LLC-PK1 cells [7]. In addition, methyl nomilinate was reported to inhibit the proliferation of MCF-7 ER+ human breast cancer cells with an IC 50 of 0.01 μg/ml [30].…”
Section: Limonoid As a Potential Ache Activity Inhibitormentioning
confidence: 96%
See 4 more Smart Citations
“…In our previous study, we found that methyl nomilinate showed an anti-inflammatory effect by inhibiting NO production by LPS-activated RAW 264.7 macrophages and significantly abrogated cisplatin-induced nephrotoxicity in LLC-PK1 cells [7]. In addition, methyl nomilinate was reported to inhibit the proliferation of MCF-7 ER+ human breast cancer cells with an IC 50 of 0.01 μg/ml [30].…”
Section: Limonoid As a Potential Ache Activity Inhibitormentioning
confidence: 96%
“…1). The compounds were identified as methyl nomilinate (1) [15], limocitrunshin (2) [7], nobiletin (3) [16], kaempferol 3-O-rutinoside (4) [17], limocitrin 3-glucoside (5) [18], kaempferol 3-(2 G -rhamnosylrutinoside) (6) [17], didymin (7) [19], (2S)-narirutin 4'-Oglucoside (8) [20] and naringenin 7-O-rutinoside (9) [21], respectively, based on comparison of their spectroscopic and physical data with those previously reported as well as by measurement of their specific rotations.…”
Section: Isolation and Structural Elucidation Of Compoundsmentioning
confidence: 99%
See 3 more Smart Citations